Profil Mutu Karagenan Kappaphycus alvarezii asal Pulau Semau pada Pengeringan Oven dan Sinar Matahari Berdasarkan Analisis Kadar Air dan Kandungan Karagenan - Chatrin Lenggu; Muntasir Muntasir; Mathias N. Kolobani (LPPM Universitas Abdurrab, 2026)
Kappaphycus alvarezii is the primary source of carrageenan widely utilized in pharmaceutical, food, and cosmetic industries. Carrageenan quality is significantly influenced by post-harvest drying methods. This study aimed to analyze effect of drying methods on moisture content and carrageenan content of red variety K. alvarezii from Letbaun Village, Semau Island, East Nusa Tenggara. A quantitative descriptive design was applied using two treatments: natural sun drying for ±3 days and oven drying at 60°C for 48 hours. Moisture content was determined by gravimetric method, while carrageenan content was quantified using High Performance Liquid Chromatography (HPLC) after alkaline extraction with 8% KOH. Statistical analyses were performed using Shapiro–Wilk test, Levene's test, and independent sample t-test (α = 0.05). Oven drying yielded a moisture content of 27.32% and a mean carrageenan content of 25.98%, whereas sun drying yielded 28.85% moisture and 24.13% mean carrageenan. Both methods complied with SNI 2690:2015 standards (≤ 30%). The independent t-test indicated no statistically significant difference between two methods (p = 0.471; p > 0.05), although oven drying numerically produced higher carrageenan content. Oven drying is recommended as a more controlled and consistent post-harvest alternative for producing high-quality carrageenan raw materials for pharmaceutical applications.